2007
DOI: 10.1016/j.pupt.2006.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Ciclesonide is more effective than budesonide in the treatment of persistent asthma

Abstract: Background: Ciclesonide is a lung-activated inhaled corticosteroid that provides effective control of persistent asthma. The objective of this study was to compare the efficacy and safety of once-daily ciclesonide versus once-daily budesonide in patients with asthma. Methods:A total of 399 patients with asthma were randomised to receive once-daily ciclesonide 320 µg ex-actuator (equivalent to 400 µg ex-valve) or once-daily budesonide 400 µg for 12 weeks. The primary endpoint was forced expiratory volume in 1 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…So far, most clinical studies with HFA‐ciclesonide have focused on standard lung function parameters such as FEV 1 or peak flow. In these studies, HFA‐ciclesonide showed similar efficacy to fluticasone propionate (FP) or budesonide . Interestingly, when looking at other parameters such as exhaled NO or QoL, HFA‐ciclesonide showed better results than FP.…”
Section: Treatment For Small Airway Inflammation – Clinical Implicationsmentioning
confidence: 93%
“…So far, most clinical studies with HFA‐ciclesonide have focused on standard lung function parameters such as FEV 1 or peak flow. In these studies, HFA‐ciclesonide showed similar efficacy to fluticasone propionate (FP) or budesonide . Interestingly, when looking at other parameters such as exhaled NO or QoL, HFA‐ciclesonide showed better results than FP.…”
Section: Treatment For Small Airway Inflammation – Clinical Implicationsmentioning
confidence: 93%
“…The efficacy of once-daily dosing with ciclesonide has been indicated in a number of clinical trials in children, adolescents and adults with asthma in comparison with placebo, BUD and FP [78][79][80][81]. Furthermore, several clinical trials have demonstrated a low incidence of oropharyngeal candidiasis and no appreciable adverse effect on endogenous cortisol secretion after short-and long-term treatment of asthma with ciclesonide at doses ranging 80-1,280 mg (ex-actuator) [82][83][84][85][86][87][88].…”
Section: Modern and Emerging Inhaled Corticosteroidsmentioning
confidence: 99%
“…From the studies it was found that once-daily ciclesonide is more effective than once-daily budesonide in improving FEV 1 , FVC and PEF. Ciclesonide also had an earlier onset of action than budesonide in patients with persistent asthma [56].…”
Section: Chronotherapy Of the New-generation Aerosol Corticosteroid Mmentioning
confidence: 94%